2015
DOI: 10.1186/s12877-015-0068-2
|View full text |Cite
|
Sign up to set email alerts
|

Excessive daytime sleepiness and falls among older men and women: cross-sectional examination of a population-based sample

Abstract: Background: Excessive daytime sleepiness (EDS) has been associated with an increased risk for falls among clinical samples of older adults. However, there is little detailed information among population-representative samples. The current study aimed to assess the relationship between EDS and falls among a cohort of population-based older adults. Methods: This study assessed 367 women aged 60-93years (median 72, interquartile range 65-79) and 451 men aged 60-92years (median 73, interquartile range 66-80) who p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
35
2
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 55 publications
5
35
2
9
Order By: Relevance
“…The effect of BMI on falls in this dataset was explored previously and was not found to have an influence, but the effect of fall‐related comorbidities or medication effect on falls cannot be excluded. The current findings corroborate those of other larger studies that have shown that reporting daytime sleepiness have a significantly higher percentage of falls . The ESS cutoff used in the current analysis was more conservative than in those larger cohort studies (≥10), yet 48% of participants with daytime sleepiness reported falling in the previous year, which may indicate the importance of subjective sleep complaints in this population.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The effect of BMI on falls in this dataset was explored previously and was not found to have an influence, but the effect of fall‐related comorbidities or medication effect on falls cannot be excluded. The current findings corroborate those of other larger studies that have shown that reporting daytime sleepiness have a significantly higher percentage of falls . The ESS cutoff used in the current analysis was more conservative than in those larger cohort studies (≥10), yet 48% of participants with daytime sleepiness reported falling in the previous year, which may indicate the importance of subjective sleep complaints in this population.…”
Section: Discussionsupporting
confidence: 87%
“…Parent Study N= 120 falls. 44,45 The ESS cutoff used in the current analysis was more conservative than in those larger cohort studies (≥10), 44,45 yet 48% of participants with daytime sleepiness reported falling in the previous year, which may indicate the importance of subjective sleep complaints in this population. The analysis showed that, even after controlling for various covariates, daytime sleepiness is related to slower gait speed.…”
Section: Participants With Ess Data N=116mentioning
confidence: 87%
“…Other factors that increase the risk of falls through effects on neurological and cognitive function have also been identified, such as excessive daytime sleepiness, dizziness, fear of falling and depression (Bath et al, 2000;Hayley et al, 2015;Iinattiniemi et al, 2009;Painter et al, 2012;Williams et al, 2015b). However, there has been little research in the area of anxiety as a risk factor for falls.…”
Section: Introductionmentioning
confidence: 99%
“…7 A cross-section study demonstrated that women with excessive daytime sleepiness have reported at least one previous fall. 8 Recent literature showed that men with short sleep duration had increased risk of fall, 9 and, in adolescents, sleep deprivation had increased falls in different conditions. 10 The effects of sleep deprivation cause significant harm to self-regulation abilities that influences attention, decision making and impulsiveness, 10 this aspect has detrimental input in outcome falls in all ages.…”
mentioning
confidence: 99%
“…10 The effects of sleep deprivation cause significant harm to self-regulation abilities that influences attention, decision making and impulsiveness, 10 this aspect has detrimental input in outcome falls in all ages. 8,10 The relationship between sleep problems and risk of falls can be influenced by several factors, such as associated diseases, depression, balance problems, impaired cognitive functions, and use of medication. Health professionals should pay more attention to the mechanisms that cause sleep deprivation and provide non-drug interventions that improve both risk of falls and sleep problems.…”
mentioning
confidence: 99%